Anatomy, Relationships, and Paleobiology of Cambaytherium (Mammalia, Perissodactylamorpha, Anthracobunia) from the lower Eocene of western India. (11th November 2019) - Rose, Kenneth D.; Holbrook, Luke T.; Kumar, Kishor; Rana, Rajendra S.; Ahrens, Heather E.; Dunn, Rachel H.; Folie, Annelise; Jones, Katrina E.; Smith, Thierry
ABSTRACT: The anatomy of Cambaytherium, a primitive, perissodactyl-like mammal from the lower Eocene Cambay Shale Formation of Gujarat, India, is described in detail on the basis of more than 350 specimens that represent almost the entire dentition and the skeleton. Cambaytherium combines plesiomorphic traits typical of archaic ungulates such as phenacodontids with derived traits characteristic of early perissodactyls. Cambaytherium was a subcursorial animal better adapted for running than phenacodontids but less specialized than early perissodactyls. The cheek teeth are bunodont with large upper molar conules, not lophodont as in early perissodactyls; like perissodactyls, however, the lower molars have twinned metaconids and m3 has an extended hypoconulid lobe. A steep wear gradient with heavy wear in the middle of the tooth row suggests an abrasive herbivorous diet. Three species of Cambaytherium are recognized: C. thewissi (∼23 kg), C. gracilis (∼10 kg), and C. marinus (∼99 kg). Body masses were estimated from tooth size and long bone dimensions. Biostratigraphic and isotopic evidence indicates an age of ca. 54.5 Ma for the Cambay Shale vertebrate fauna, the oldest Cenozoic continental vertebrate assemblage from India, near or prior to the initial collision with Asia. Cambaytheriidae (also including Nakusia and Perissobune ) and Anthracobunidae are sister taxa, constituting the clade Anthracobunia, which is sister to Perissodactyla. We unite them in a new higher taxon, Perissodactylamorpha. The antiquity and occurrence of Cambaytherium —the most primitive known perissodactylamorph—in India near or before its collision with Asia suggest that Perissodactyla evolved during the Paleocene on the Indian Plate or in peripheral areas of southern or southwestern Asia.